Finding youth - Andrews, Gertrude Nelson (Salt Lake City, UT : Project Gutenberg, 2023)
"Finding Youth: A Human Experience" by Nelson Andrews is a reflective narrative written in the early 20th century. This book falls under the genre of personal essay or self-help literature and explores the process of rediscovering youthfulness and vitality in the later years of life. The narrative centers around the universal quest for meaning and purpose as one ages, illustrating that the spirit of youth can be cultivated regardless of physical age. The story follows Harvey Allen, a 60-year-old man who faces the loss of his job in a printing plant and the ensuing identity crisis. The narrative delves into his struggles with feelings of obsolescence and declining self-worth, as he grapples with societal views on aging. However, through a series of interactions and revelations$1 (Bincluding conversations with a caring wife and the wise but seemingly misguided Miss Marsh$1 (BHarvey discovers a guiding "Voice" that encourages him to reclaim his youthful spirit. This internal dialogue propels him to embrace new adventures, ultimately leading him to a fulfilling role in a small newspaper office, where he finds renewed purpose. The culmination of his journey results in the establishment of a "Youthland" colony, a sanctuary for older individuals to thrive creatively and socially, further underscoring the book's message that age is but a number, and that the zest for life can and should continue into the later years. (This is an automatically generated summary.)s
Release date is 2023-02-04
Bob Taylor, hekula03 and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Old age